HUMANISME SEBAGAI FILSAFAT HUKUM ISLAM - Nur Kholis (Isti`dal : Jurnal Studi Hukum Islam, 2014)
There are two (2) issues of humanism regarding to the philosophy of Islamic law. First, humanism either as the movement of the humanities or the schools of philosophy, in the West (Christian) and the East (Islam)-grows and evolves in the dialectic of human life that is characterized by tendency to deny the others. Fundamental rights of human in the socio-cultural history is proved repeatedly crushed by the interests of abstract theology, exclusive ideology, massive feudalism, and lack of empathy for the weak. On the basis of this ridiculous "crisis of humanitarian vision", humanism exists (inductively) to save humanity through the "movement of consciousness" of the human's dignity height. Secondly, after humanism is established in a form of conception, humanism need to be spread into the real life of humanity. At this stage the deduction problem occurs, in this case, occurs in discourse of Islamic law philosophy as well. Given humanism ontology is consciousness of human dignity, and its epistemology refers to the entire human potency and nature, then humanism axiology can be articulated in the philosophy of Islamic law in favor of awareness, potential, as well as the nature of humanity itself.Keywordshuman, humanism, the West, Islam, philosophy of Islamic law Terdapat 2 (dua) persoalan tentang humanisme dalam kaitannya dengan filsafat hukum Islam. Pertama, humanisme??baik sebagai gerakan ilmu-ilmu humaniora maupun sebagai aliran filsafat, di Barat (Kristen) maupun di Timur (Islam)??tumbuh dan berkembang dalam dialektika kehidupan manusia yang diwarnai kecenderungan menafikan sesama. Hak-hak mendasar manusia dalam sejarah sosial- kebudayaannya terbukti berulangkali tergilas oleh kepentingan teologi yang abstrak, ideologi yang eksklusif, feodalisme yang massif, serta minimnya empati terhadap golongan yang lemah. Atas dasar ??krisis visi kemanusiaan? inilah humanisme mengada (secara induktif) untuk menyelamatkan manusia melalui ??gerakan kesadaran? akan tingginya harkat dan martabat manusia. Kedua, setelah humanisme terbangun dalam sebuah wujud konsepsi, humanisme perlu dipribumisasikan ke dalam kehidupan riil kemanusiaan. Pada tahap inilah persoalan deduksi terjadi, termasuk dalam hal ini juga terjadi dalam diskursus filsafat hukum Islam. Mengingat ontologi humanisme adalah kesadaran (consciousnes) akan kemuliaan manusia, dan epistemologinya mengacu pada seluruh potensi dan tabiat kemanusiaan manusia, maka aksiologi humanisme dapat diartikulasikan dalam filsafat hukum Islam dengan mengunggulkan kesadaran, potensi, serta tabiat kemanusiaan itu sendiri.